Mewujudkan Layanan Publik yang Adil dan Inklusif: Kendala Bahasa dan Etika Kewarganegaraan Birokrasi - Al Kausar, Jefri; Alan Fajar, Syahrier; Wira, Anshori; Arissy Jorgi, Sutan (Journal of Civic Education, 2025)
The challenge of language barriers in Indonesian public service interactions is discussed in this article regarding technical communication failure and critical issue of bureaucratic ethics and the violation of civil rights. The study asserts that problems such as rigid bureaucratic language, inaccessible channels, and unaddressed public feedback constitute a systemic failure of the public service apparatus to uphold principles of inclusive public service and non-discrimination. Employing a Systematic Literature Review (SLR) methodology, which involved screening publications from the Scopus and Sinta databases (2020–2025), the research protocol was designed to be systematic and reproducible. The synthesis of findings reveals that these operational shortcomings are not merely technical failings but are instead a clear manifestation of a deficiency in the Civic Virtue of civil servants, who bear the ethical responsibility to bridge multicultural differences rather than perpetuate exclusionary practices. The study concludes by underscoring the urgent necessity for bureaucratic paradigm reform, specifically recommending the mandatory development of a Civic Ethics Curriculum for civil servants that explicitly cultivates the values of inclusivity, public empathy, and a comprehensive awareness of citizens' rights within a diverse, democratic context.